Policy on technical and vocational education and training: Technical and vocational education and training for economic advancement - Guyana. Ministry of Education and Cultural Development (Ministry of Education and Cultural Development, Guyana, 1993)
This policy paper articulates a major development plan for the further development and efficient and effective delivery of technical and vocational education and training. It advocates better managerial control; the establishment of facilities at the Cyril Potter College of Education for the initial training of technical teachers; organized staff development activities; and overhauled and expanded physical capacity, the establishment of modularized curriculum, and a reorganized guidance and counselling service.
Keywords: technical education